Sosialisasi Pengolahan Limbah Organik Rumah Tangga Melalui Budidaya Magot di Desa Pandeyan, Kecamatan Grogol, Kabupaten Sukoharjo - Tri Atmoko, Nugroho; Suryono, Edy; Besar Riyadi, Tri Widodo; Teofilus Riyadi, Natanael; Awan, Sang Alang; Wicaksono, Bagas; Yuniarta, Fajar; Bagus Nugroho, Taufik; Putra Tegar Permata, Septian (Jurnal Suara Pengabdian 45, 2023)
Organic waste is an environmental problem, especially in the villages of Pandeyan, Grogol, Sukoharjo, so there is a need to solve this problem through direct community activities. One solution is the socialization activity on organic waste processing through magot cultivation in Pandeyan village. With this socialization, it is hoped that the community will gain further understanding regarding magot cultivation as an effort to process household organic waste to make it more useful. The socialization activity was conducted at the Pandeyan village office on August 30, 2023. To measure the success of socializing organic waste processing through magot cultivation, an evaluation was carried out using a questionnaire method distributed to participants. From the questionnaire results, it was found that 88.9% of the total participants understood magot cultivation. Meanwhile, if you look at the potential of organic waste in each household participating in this socialization, it is possible to process it through magot cultivation. However, there is still a need for assistance and further understanding regarding magot cultivation because there is still a stigma that maggots have a maggot-like shape and are not suitable for cultivation.